HAMAS AND HEZBOLLAH AS ACTORS: COMPARATIVE ANALYSIS AND PROSPECTS OF INTEGRATION IN THE WORLD ORDER - Vladimir M. Morozov; Aysha B. Khachirova (Сравнительная политика, 2018)
The article is devoted to the problem of non-state entities in a changing nature of world politics. Hamas and Hezbollah are seen as major non-governmental actors in the Middle East with great potential to infl uence regional political processes including the Palestinian-Israeli peace talks. The authors made an attempt to conduct comparative analysis of those movements’ compliance with the benchmarks of an actor (drafted by J. Nye, R. Keohane and other prominent political scientists) so as to assess its roles and positions in the region. Suggestions on shaping foreign policy towards those nonstate actors were made and strategies of its incorporation in the world order were investigated. The authors described negative and positive projections of such an engagement of Hamas and Hezbollah in the regional processes and gave their perspective on the feasibility of each scenario.